Three new species of the genus Empidideicus Becker, 1907 (Diptera, Mythicomyiidae) from Iran with the first record of the subgenus Cyrtoides Engel, 1933 - Gharali, Babak; Evenhuis, Neal L.; Moghbeli, Sajjad (Zootaxa, 2025)
Empidideicus (Empidideicus) ferrarius Gharali, Evenhuis & Moghbeli sp. nov.; Empidideicus (Cyrtoides) primitus Gharali, Evenhuis & Moghbeli sp. nov. and Empidideicus (Cyrtoides) reemeri Gharali & Evenhuis sp. nov. are described based on specimens collected from Iran by white pan trapping. Empidideicus primitus sp. nov. and E. reemeri sp. nov. mark the first records of the subgenus Cyrtoides from Iran, and with the description of these new species, the subgenus now contains five species in the World. Dichotomous keys to all species of the genus Empidideicus occurring in Iran and species of the subgenus Cyrtoides worldwide are presented.